Suporte social humanístico-administrativo ao fim de vida para o idoso e família: alguns subsídios em uma revisão integrativa da literatura - Merchan, Ana Michela Lista (2019)
The present study aims to reflect on the conception of family or caregiver procedures at the end of life of an elderly person, and what founds such procedures manifest in the literature retrieved on this theme. In this paper, an integrative approach to the literature in the Virtual Health Library (VHL) was reviewed to answer the question: “How to deal concretely with the end-of-life situation of a old man?" The following descriptors were used: “Assistance / Shared Decision Making at End of Life”; “Care for patients in a situation of death”; “Death / Good Death; Death / Elderly”; “Dignity in the process of dying”; “Death and Thanatology”; “Autonomy in the choices of the elderly”; “Training in the face of loss and death”. This survey, after systematization in the light of data collection criteria, allowed us to find five scientific articles, which constituted categories of meaning that were named as follows: (1) Reflection on human finitude; (2) Analysis of the end-of-life situation of an elderly person who assists them; (3) Humanization of end-of-life care; (4) Training of professionals in various areas to deal with people in situations of loss and death. Finally, it was found that there are different ways of understanding the end-of-life situation, with each person inscribing something of their own; There are also various procedures for dealing with situations of loss and death, depending on the uniqueness of each person involved, and of each professional, which varies according to their life history, and how this subject fits into society. Subsidies are presented for the training of health and education professionals to deal with people who experience situations of loss and death